Childern’s Sense Of Place Base On The Kampung-Forming Elements In Pakisaji Art Kampong - Anggie Nabila Pitaloka; Jenny Ernawati (Jurnal Mahasiswa Jurusan Arsitektur, 2021)
In Malang, there are five art villages and Kampong Seni Pakisaji considered as one of them. This village held a long history and culture which has been deeply rooted for its people. The sole purpose of this research is to evaluate every element in forming the village which affecting child sense of place element, so that in the future any improvement made in this area will have to consider its’ use of space. There are several elements considered as forming elements of a village and those are physical element, social element, and personal element. Combination of those three elements create meaning of space. In this research, writer using architectural psychology approach to know user’s perspective specifically children perspective using deep interview method and cognition mental mapping. Qualitative descriptive analysis will be use as the analysing method in terms of defining the key terms and naration. The result of the analysis shows that social aspect having more effect on the children’s sense of that place. In conclusion, forming elements affecting Kampong Seni Pakisaji consecutively are social, personal and physical.